Implementation of Advocate Special Professional Education Program (PKPA) by PKPA Institutions, Indonesian Advocates Association (AAI) Bandung - Gintings, Abdorrakhman; Bulan, Renova Rumondang; Sanusi, Achmad; Hanafiah, Nanang (Advances in Social Sciences Research Journal, 2020)
The purpose of this study is to answer two main questions, which are: a) aspects of organizing Advocate Special Professional Education Program organized by PKPA institutions and the Indonesian Advocates Association and b) efforts to improve and follow up programs organized by the Indonesian Advocates Association. The data of this study were collected from 49 respondents consisted of 1 Head of Bandung City institution, 1 Head of the program division, 2 program coordinators, 15 facilitators/lecturers and 30 participants in Bandung City education and training program. Data that has been collected from the interview process and questionnaire dissemination are then enriched and triangulated by monitoring the sustainability of program implementation which includes program planning, program implementation, program evaluation and verifying documents on program implementation plans, human resources (HR), Infrastructure, and evaluations on post-education of advocate profession. The results of the data analysis show that Bandung's advocate professional education combines two methods by combining academics and practitioners so as to produce professional advocates. In conclusion, the Advocate Special Professional Education Program remains consistent with Law Number 18 of 2003 concerning Advocates, this is due to the increasing number of graduates in law majors who are interested become lawyers so that they can solve problem correctly. It is recommended that advocate professional education services organized by the institution be followed up with statistics data of participant that have passed, facilities and other learning tools that are in accordance with the procedures of the institution.